Utilization of TikTok Shop Interactive Features and Their Impact on Consumer Purchasing Decisions - Dahniar, Sri; Anugra, Widya; Sakinah, Adinda; Febrianti, Widia; Hasan, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2023)
TikTok, a widely used social media platform, recently introduced the TikTok Shop interactive feature, enabling users to shop directly from videos. This study, employing a quantitative descriptive method, gathered data through surveys and questionnaires, focusing on consumers who accessed TikTok Shop. The findings reveal a significant positive impact of TikTok Shop's interactive features on consumer purchasing decisions. Users frequently engaging with products showcased in TikTok Shop videos are more likely to make purchases. Additionally, recommendations and reviews from other users on the platform significantly influence consumer purchase decisions